'Hell-like' exoplanet experiences rocky rain and supersonic wind. (March 2021) - James, Chaneil
Abstract : A fiery exoplanet located barely a million kilometres from its parent star is covered by magma oceans and has an atmosphere of vaporized rock on its "day" side, while its "night" side remains cold enough for glaciers to form.